The Impact of Borrower and Loan - Khan, Mohamed Hoosain (My University, 2011)
In South Africa, there is currently little research available on mortgage default and the determinants of default. The purpose of this research was to evaluate and distinguish between mortgage specific factors (including borrower and loan characteristics), driving mortgage default patterns in South Africa. This study intended to provide guidance to the South African banking industry (i.e. banking institutions), the South African Reserve Bank (policy maker and regulator), and the broader South African population in general. In addition, the results of the study can be utilised by banking institutions as inputs into their origination scorecard, policy rules and risk-based pricing models. Due to the sensitivities around financial institution’s data in South Africa, the sample used for this study was all current (on book) mortgage loans from an anonymous (single) financial institution in South Africa. Also, due to the practical availability of data, the sample period covered all current loans from said financial institution from August 2006 to December 2008, with information covering each loans default or non-default status during that time period. Based on the review of the literature surrounding mortgage defaults, five hypotheses were formulated. Only 1 of the 5 variables was found to be a good differentiator of mortgage default in South Africa. Current Loan-To-Value (LTV) was found to be the most critical and by far the largest contributor to the model’s ability to differentiate defaults. It was found that the higher the Current LTV, the more likely those borrowers would default. This finding is in line with conventional wisdom in the mortgage industry, in that loan-to-value ratios are positively correlated with mortgage default. The Age of the mortgage (i.e. account age in months since loan origination), Instalment to Income (ITI), Borrower age (years), Borrower Income and Balance Outstanding were found to be irrelevant in contributing to the model’s ability to differentiate mortgage defaults. Also, Balance (Loan) Outstanding was found to be the variable having the least impact on the model’s ability to differentiate iii mortgage defaults. In summary, given that Current LTV (loan characteristic), was found to be the only suitable variable in differentiating mortgage defaults, the conclusion is that only “Loan” characteristics (i.e. Loan to value) impact on mortgage defaults in South Africa. Furthermore, it is the “equity” theory that describes mortgage defaults, and not the “ability to pay” theory of default
MBA - WBS
Keywords: Mortgages, South Africa; Mortgage defaults, South Africa